DESAIN TAMAN KULINER UNTUK PEDAGANG KAKI LIMA YANG INOVATIF DI TEPI SUNGAI, SURABAYA - Gunawan Tanuwidjaja; El Sadday A. Oktovianto; Joyie Joyie; Felicia Lisandra S. (SHARE: Journal of Service Learning, 2015)
Nowadays, the owners of Small and Medium Enterprises (SMEs), especially food street vendors (PKL) faced difficulty to increase the operational scale and productivity. Besides that, the street vendors are still not able to compete, because of limited architectural design, human resources, and marketing strategies. Therefore, street-food center design, which integrated with Urban Park was needed with attention of cleanliness, comfort, neatness aspects and producing positive image. In the paper, design process street-hawker kiosk was started with exploration into traditional food restaurants and traditional food vendors using visual research. The design was based on the principles of inclusive design such as: User Centered, Equitable use but Reasonable, Simple and Intuitive Use, Low Physical Effort, and Prohibition of Usage Error.